Pembaruan Teknologi Informasi Pada Pendidikan TK di Kotim - Rani Ayu Sampita Sari; Nurahman Nurahman (Journal of Computer System and Informatics (JoSYC), 2020)
Kindergarten education is a form of formal education in early childhood education. Kindergarten, abbreviated as Kindergarten, is a form of early childhood education unit in the formal education pathway that organizes educational programs for children aged 5 and 6 years. It makes it difficult for parents to find information and record and lose data for teaching staff. With this system, it is hoped that Kindergarten, which previously made it difficult for parents to obtain information, can now be accessed online